2010
DOI: 10.1111/j.1463-1318.2010.02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified loose‐seton technique for the treatment of complex anal fistulas

Abstract: The technique shows excellent results in the treatment of complex anal fistulas with conservation of fecal continence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A fistulectomy has been reported by many clinical studies as a sufficient surgical technique for successful management of a simple or a low transsphincteric anal fistula. When an advanced complicated transsphincteric or suprasphincteric fistula is encountered, many operative options, including the utilization of advancement flaps, application of an anal plug, the use of fibrin glue, radiofrequency ablation, intersphincteric fistula tract ligation, or application of a loose seton, may be involved [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A fistulectomy has been reported by many clinical studies as a sufficient surgical technique for successful management of a simple or a low transsphincteric anal fistula. When an advanced complicated transsphincteric or suprasphincteric fistula is encountered, many operative options, including the utilization of advancement flaps, application of an anal plug, the use of fibrin glue, radiofrequency ablation, intersphincteric fistula tract ligation, or application of a loose seton, may be involved [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eitan et al [13] reported an incontinence rate of 5% after loose seton placement. In another study, the incontinence rate was reported to be 0%-8%, and only minor complaints were observed in 60% of the patients [4, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the success rate after loose seton placement is between 44%-78% [4, 15]. Success rates, of course, depend on the location of the fistula, and they are reported to be 66% and 88% in the presence of anterior and posterior fistulae, respectively [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations